Let's analyze Suzie's steps to see if she solved the equation correctly.
The original equation is:
\[ 9x - 5 = 14(16x + 60) \]
Step 1: Distribute 14 to (16x + 60)
Here, Suzie incorrectly stated that she distributed \( \frac{1}{4} \). The correct distribution of 14 should be:
\[ 14 \cdot 16x + 14 \cdot 60 = 224x + 840 \]
Thus, the equation should be:
\[ 9x - 5 = 224x + 840 \]
Step 2: Move 224x to the left side.
Using the subtraction property of equality:
\[ 9x - 224x - 5 = 840 \] \[ -215x - 5 = 840 \]
Step 3: Move -5 to the right side using the addition property of equality.
\[ -215x = 840 + 5 \] \[ -215x = 845 \]
Step 4: Divide by -215.
\[ x = \frac{845}{-215} \] \[ x = -\frac{845}{215} \] (This simplification would give a final answer)
Since Suzie made an error in Step 1, her entire following solution is based on that mistake.
Upon review of her original steps, we conclude:
- Suzie made a mistake on Step 1 — she should have distributed 14 to both terms in the parentheses.
So the correct response is:
Suzie made a mistake on Step 1 - she should have distributed the 1/4 to 60 as well. (This option slightly misstates what should be 14, but combines distribution works).